Conservation genetics of the steno-endemic Chorthippus lacustris (Orthoptera: Acrididae) - Toli, Elisavet-Aspasia; Zacharopoulou, Panoraia; Bounas, Anastasios; Kati, Vassiliki; Sotiropoulos, Konstantinos (Journal of insect conservation, 2023)
Invertebrate populations are amongst the most widespread species, inhabiting a variety of habitats, however there is limited conservation effort due to the scarce knowledge on their population genetics. Here, we assess levels of genetic diversity and population structure of the Epirus dancing grasshopper ( Chorthippus lacustris ), a steno-endemic species, located in Northwest Greece, exhibiting a fragmented distribution. By utilizing two mitochondrial genes and amplified fragment length polymorphisms (AFLPs), we detected moderate to high levels of genetic diversity of the focal populations. Haplotype network analysis revealed the existence of private haplotypes with low genetic differentiation suggesting a sudden expansion of the species in the study area with subsequent isolations on suitable habitats. Despite the low genetic differentiation between the studied populations, our data further suggest a subtle subdivision of the populations and the existence of three genetic clusters. Implications for insect conservation : Our study is the first to provide insights into the population genetics of the steno-endemic grasshopper C. lacustris , highlighting the importance of preserving focal populations. The species inhabits areas subject to high changes in land use and fragmentation. We argue that the preservation and management of suitable habitats is essential for the viability of the grasshopper populations.